Martin Luther – Held of skurk? - Wessels, G. Francois 1950- (2019)
The article investigates whether Martin Luther was anti-Semitic, and if so, what effect it had on his theology and ministry. First the article investigates the written comments of Luther in his works, from his article in 1523 That Jesus was born a Jew, in which Luther still cherished the hope that Jewish people would soon turn to accept the good news of the Gospel - as re-discovered by Protestantism, once it had been properly explained to them. The article then briefly describes how - with reference to Luther’s less friendly later articles - Luther’s anger against Jews grew as the years passed by without any significant change in the European Jewish community towards Jesus Christ. The article argues that Luther’s writings were certainly anti-Jewish (being against the Jews because they refused to accept the blessing of the Christian faith), but not necessarily anti-Semitic (being against Jews simply because they were Jews). In the second part of the article the author investigates how Luther’s interpretation of Paul was influenced by his own dramatic discovery and interpretation of the concept of the “righteousness of God”, which blessed Luther in his Christian faith, but unfortunately also cloudedhis vision, with the result that Luther tended to understand the “righteousness of God” only in forensic terms. That theological blind spot unfortunately kept Luther from fully understanding Paul’s emphasis that the “righteousness of God” also have a powerful social impact.